Comparison of pharmacokinetic profiles of single and multiple doses of a slow release Oros oxprenolol delivery system in young normotensive and elderly hypertensive subjects. - Bradbrook, I D (1986)
Oxprenolol in an Oros 8/130 sustained release osmotic pump system (equivalent to 120 mg oxprenolol hydrochloride in a conventional formulation and releasing 8 mg h-1) was given to eight normal young subjects (mean age 23 years) and eight elderly hypertensive patients (mean age 77 years). The plasma concentration-time profiles of oxprenolol were determined over 32 h using gas liquid chromatography after the initial dose and following seven doses. The elderly patients had a significantly higher AUC and maximum plasma oxprenolol concentration following both the first and final doses studied. It is unlikely that this difference is due to a prolonged absorption phase in the elderly patients. Reduced drug clearance seems the most probable explanation.